2022
DOI: 10.1080/21655979.2022.2075300
|View full text |Cite
|
Sign up to set email alerts
|

FAM198B promotes colorectal cancer progression by regulating the polarization of tumor-associated macrophages via the SMAD2 signaling pathway

Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors. Tumor-associated macrophages (TAMs) promote the progression of CRC, but the mechanism is not completely clear. The present study aimed to reveal the expression and function of FAM198B in TAMs, and the role of FAM198B in mediating macrophage polarization in CRC. The role of FAM198B in macrophage activity, cell cycle, and angiogenesis was evaluated by CCK-8 assay, flow cytometry, and vasculogenic mimicry assay. The effects of FAM198B on macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In colorectal cancer, the tumor suppressor gene NIT1 is realized by activating the SMAD2/3 signaling pathway [23]. SMAD2 can promote the development of CRC by regulating the polarization of tumor macrophages [24]. In this study, SMAD2 expression in CRC was low, which was SMAD3 plays the dual role of oncogene and tumor suppressor gene in tumor formation, and can be used as a prognostic marker for tumors [22].…”
Section: Discussionmentioning
confidence: 68%
“…In colorectal cancer, the tumor suppressor gene NIT1 is realized by activating the SMAD2/3 signaling pathway [23]. SMAD2 can promote the development of CRC by regulating the polarization of tumor macrophages [24]. In this study, SMAD2 expression in CRC was low, which was SMAD3 plays the dual role of oncogene and tumor suppressor gene in tumor formation, and can be used as a prognostic marker for tumors [22].…”
Section: Discussionmentioning
confidence: 68%
“…FAM198B also functions in the tumour microenvironment. For example, Zheng et al ( 53 ) observed that the expression level of FAM198B in macrophages of colon cancer tissues correlated with patient prognosis. FAM198B regulates M2 polarisation in macrophages and promotes colon cancer progression by targeting SMAD2 ( 53 ).…”
Section: Celf2 Affects Ferroptosis Through the Mapk Signalling Pathwaymentioning
confidence: 99%
“…For example, Zheng et al ( 53 ) observed that the expression level of FAM198B in macrophages of colon cancer tissues correlated with patient prognosis. FAM198B regulates M2 polarisation in macrophages and promotes colon cancer progression by targeting SMAD2 ( 53 ). Existing research demonstrates that FAM198B exerts its tumour-suppressive effects mainly by inhibiting the ERK/MAPK pathway ( 51 , 52 ); however, the exact mechanisms involved remain elusive.…”
Section: Celf2 Affects Ferroptosis Through the Mapk Signalling Pathwaymentioning
confidence: 99%
“…However, recent reports showed that FAM198B can also promote colorectal cancer (CRC) progression ( 99 ). The upregulation of FAM198B was found in macrophages and was considered associated with the poor prognosis of CRC.…”
Section: The Role Of the Secretory Pathway Kinases Or Kinase-like Pro...mentioning
confidence: 99%